Astronomia e Educação Ambiental: uma proposta na busca pela consciência planetária - Silva Neto, Natan Pires da (Universidade Federal de São Carlos, 2020)
The objective of this research is to investigate the application of Astronomy contents in Environmental Education (EE) and to contribute to the development of planetary or ecological awareness. For this purpose, an intervention study of experimental nature was developed. A didactic sequence in Astronomy was proposed to contribute to the development of ecological awareness among students. Initially, a bibliographic review of theses and dissertations, articles published in journals, and works presented in selected events was carried out. Qualitative data was analyzed in order to investigate the characteristics of pedagogical practices, the acquisition of knowledge, and the involvement and participation of students in the production of the proposed activities, such as thematic workshops. With the activities, it was possible to detect the acquisition of knowledge and the increase in students’ vocabulary related to astronomical concepts. It was also noted that astronomical scientific knowledge contributes to the development of ecological awareness, considering the interface of these areas as a motivation for students to incorporate them to their daily lives and to improve environmental discussions. The environment is addressed as an important resource for the survival of all living beings, and EE is approached as a teaching and learning process to raise awareness in the preservation and conservation of these resources. The Astronomy content was developed from the individual's vision and perception. The Solar System was discussed as a portion of the Universe with pedagogical strategies in the practice of activities. These activities used a topocentric approach and a holistic perspective. Through classroom discussions, during the stages, the development of ecological awareness was evidenced using the multidisciplinary potential of Astronomy. The didactic sequence motivated the students and contributed to the understanding of human belonging to the planet and of responsibility with the environment.
Astronomy and Environmental Education: a proposal for the search for planetary consciousness
Keywords: Ensino de Astronomia.; Consciência ecológica.; Educação Ambiental.; Astronomy teaching.; Ecological awareness.; Environmental education.; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM